Avaliação do impacto de instalação dos Institutos Federais de Ciência e Tecnologia nos municípios brasileiros - Oliveira, Eduardo Cândido de (2017)
The federal education network expansion specifically on what concerns the Federal Institutes of Education, Science and Technology (FIs), tends to foster local and regional development, besides the transference of technology to society. Therefore the present work has as objective to verify if the expansion of the FIs has benefited the municipalities in the educational scope. If so, the impact of the expansion policy for the involved municipalities will be dimensioned. Another fact to be verified is what elements influence a municipality to be the headquarters of an FI and if the mayor’s party has influence in that benefit. The ENEM and IDEB grades are going to be used as well as socioeconomic and educational variables for the municipalities between 2007 and 2013. Two econometric models are going to be estimated for panel data which evaluate the impact of FI installation on the two indicators. The results show that there were indeed positive effects in the ENEM and IDEB notes for the municipalities that were included in the expansion policy and also for the municipalities that are in the same micro-region. In addition, there is a greater probability of municipalities administered by PT or PMDB, since 2008, receive an FI.